At Least One-Third of Zeros of Riemann's Zeta-Function are on σ = ½ - Levinson, Norman (1974)
Starting from the derivative of the functional equation of the zeta-function, it is shown that at least one-third of the zeros of the zeta-function are on the line σ = ½.